2016
DOI: 10.1111/ecc.12559
|View full text |Cite
|
Sign up to set email alerts
|

Associations among menopausal symptoms, sleep and fatigue in Taiwanese women with endometrial cancer

Abstract: The purpose of this study was to explore the relationships among menopausal symptoms, sleep quality and fatigue in women with endometrial cancer. Participants were 95 women (mean age = 57.44 ± 10.15 years) diagnosed with endometrial cancer and who had completed their treatment before data collection. Each woman completed three structured questionnaires: the Functional Assessment of Cancer Therapy-Endocrine Symptoms (endocrine symptom subscale), the Pittsburgh Sleep Quality Index and the Functional Assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 109 publications
(164 reference statements)
2
10
0
Order By: Relevance
“…The result of the regression analysis showed that sleep quality, comorbidity and age were important predictors of fatigue. This supported the findings of past research on ovarian or breast cancer populations, which showed that survivors with poorer sleep quality (Li et al, 2017), higher comorbidity index (Jones et al, 2016) and younger age (Bifulco et al, 2012) had higher fatigue level.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The result of the regression analysis showed that sleep quality, comorbidity and age were important predictors of fatigue. This supported the findings of past research on ovarian or breast cancer populations, which showed that survivors with poorer sleep quality (Li et al, 2017), higher comorbidity index (Jones et al, 2016) and younger age (Bifulco et al, 2012) had higher fatigue level.…”
Section: Discussionsupporting
confidence: 90%
“…Our study subjects had a moderate level of fatigue similar to what was reported in previous studies (Li et al, 2017). The result of the regression analysis showed that sleep quality, comorbidity and age were important predictors of fatigue.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, after adjusting for the different treatment modalities and patient characteristics, physical fatigue levels were significantly higher among endometrial compared to breast cancer patients. Although the difference failed statistical significance after adjusting for multiple testing ( P = .17), it might be worth considering that fatigue in endometrial cancer has been found to be associated with menopausal symptoms, which are a common consequence of the surgical procedures for this type of cancer that result in estrogen deficiency 25 . Thus, hormonal pathways may be more relevant in fatigue etiology with this type of cancer than in many other cancer types.…”
Section: Discussionmentioning
confidence: 96%
“…Although the difference failed statistical significance after adjusting for multiple testing (P = .17), it might be worth considering that fatigue in endometrial cancer has been found to be associated with menopausal symptoms, which are a common consequence of the surgical procedures for this type of cancer that result in estrogen deficiency. 25 Thus, hormonal pathways may be more relevant in fatigue etiology with this type of cancer than in many other cancer types. Surprisingly, bladder cancer patients had the highest prevalence of emotional fatigue (49%) although prevalence for physical fatigue (38%) was among the lowest of all considered entities.…”
mentioning
confidence: 99%